PENGARUH TERAPI PIJAT REFLEKSI KAKI DENGAN METODE MANUAL TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KARANGREJO TIMUR WONOKROMO SURABAYA - Faridah Umamah; Shinta Paraswati (coba, 2019)
Abstract. Hypertension or high blood pressure cannot be considered a mild disease. Not only decreasing the quality of life, it can threaten patient’s self. The objective of this study was to find out the effect of the foot reflexology massage therapy with manual method on the blood pressure in patients with hypertension.The design of the study used the Quasi experimental design with the approach pretest-posttest control group design. The population of all patients with hypertension at Karangrejo Timur Wonokromo Surabaya is 38 people, and the sample was 35 people taken by simple random sampling method. The independent variable is foot reflexology massage therapy with manual method, whereas the dependent variable is the blood pressure of hypertension patients. The instrument used was a observation sheet. Statistical test using Wilcoxon test with a significance of α = 0,05. The result of Wilcoxon test showed the value of ρ = 0,001 and the value of α = 0,05 meaning that ρ < α then H0 is rejected. It means that foot reflexology massage therapy with manual method had an effect on the blood pressure of patients with hypertension. The conclusions of the study is foot reflexology therapy with manual method can lower blood pressure in hypertension patients. Expected nurses can provide counseling about prevention and treatment of hypertension either using reflexology massage therapy with manual method or with other methods. Keyword : Foot reflexology massage therapy with manual method, blood pressure, hypertension